Characteristics and outcomes of patients presenting with acute myocardial infarction and cardiogenic shock during COVID‐19. Issue 4 (7th September 2022) - Ahlers, Michael J.; Srivastava, Pratyaksh K.; Basir, Mir B.; O'Neill, William W.; Hacala, Michael; Ammar, Kareem; Khalil, Suzan; Hollowed, John; Nsair, Ali
Abstract: Objectives: To evaluate characteristics and outcomes of patients presenting with acute myocardial infarction and cardiogenic shock (AMICS) during the coronavirus disease 2019 (COVID‐19) pandemic. Background: The COVID‐19 pandemic has created challenges in delivering acute cardiovascular care. Quality measures and outcomes of patients presenting with AMICS during COVID‐19 in the United States have not been well described. Methods: We identified 406 patients from the National Cardiogenic Shock Initiative (NCSI) with AMICS and divided them into those presenting before ( N  = 346, 5/9/2016−2/29/2020) and those presenting during the COVID‐19 pandemic ( N  = 60, 3/1/2020−11/10/2020). We compared baseline clinical data, admission characteristics, and outcomes. Results: The median age of the cohort was 64 years, and 23.7% of the group was female. There were no significant differences in age, sex, and medical comorbidities between the two groups. Patients presenting during the pandemic were less likely to be Black compared to those presenting prior. Median door to balloon (90 vs. 88 min, p  = 0.38), door to support (88 vs. 78 min, p  = 0.13), and the onset of shock to support (74 vs. 62 min, p  = 0.15) times were not significantly different between the two groups. Patients presented with ST‐elevation myocardial infarction more often during the COVID‐19 period (95.0% vs. 80.0%, p  = 0.005). In adjusted logistic regression models, COVID‐19 period did not significantly associate with survival to discharge (odds ratio [OR] 1.09, 95% confidence interval [CI] 0.54−2.19, p  = 0.81) or with 1‐month survival (OR 0.82, 95% CI 0.42−1.61, p  = 0.56). Conclusions: Care of patients presenting with AMICS has remained robust among hospitals participating in the NCSI during the COVID‐19 pandemic.